WORKPIECE AND MANUFACTURING METHOD THEREOF - ZHANG CHUN-JIE (2015)
PROBLEM TO BE SOLVED: To provide a workpiece with high hardness and an excellent hydrophobic property, and a method for manufacturing the workpiece.SOLUTION: A workpiece 10 includes a substrate 11, and a diamond-like carbon film 15 that is formed on the substrate 11, and on which plural nano-sized bumps are formed. A workpiece manufacturing method includes steps of: providing the substrate 11; forming a metallic layer 13 on the surface of the substrate 11 by a vacuum deposition method; forming the plural nano-sized bumps on a surface of the metallic layer 13 by cooling the metallic layer 13; and forming the diamond-like carbon film 15, on which the plural nano-sized bumps are distributed, on an upper face of the metallic layer 13 that is subjected to a liquid nitrogen cooling treatment by the vacuum deposition method. 【課題】高硬度及び優れた疎水性を有するワーク及び当該ワークの製造方法を提供する。【解決手段】基材１１及び基材１１の表面に複数のナノレベルの突起が形成されるダイヤモンドライクカーボン膜１５を備えたワーク１０であって、基材１１を提供する工程と、真空蒸着法によって基材１１の表面に金属層１３を形成する工程と、液体窒素を用いて金属層１３を冷却することによって金属層１１の表面に複数のナノレベルの突起が形成される工程と、真空蒸着法によって、液体窒素冷却処理を経た金属層１１の上面に複数のナノレベルの突起が分布されるダイヤモンドライクカーボン膜１５を形成する工程とを備えるワークの製造方法。【選択図】図１